Farmers' perceptions of East Coast fever risk and adoption of control strategies in Kenya - Leneman, J.M.; McDermott, John J.; Okuthe, O.S.; Randolph, Thomas F. (International Society for Veterinary Epidemiology and Economics, 2000)
East Coast Fever (ECF) is a major risk and constraint to the smallholder dairy sector in Kenya. The effects of ECF can be largely controlled by the use of acaricides, animal husbandry measures, and potentially through immunisation. In Kenya, some smallholder dairy farmers apply one or more of these control strategies; however, a large number of them do not actively control the disease and accept its risks and production limitations. These decisions are influenced by farmers perceptions of both ECF risk on production and the biological and economic risks of available ECF control options. Thus, an assessment of the risk perceptions of farmers is essential in planning the delivery and assessing the adoption of ECF control programmes. To study the Kenyan smallholder dairy farmers' perception of ECF risk and their adoption of ECF control measures, four contrasting study sites were selected. These sites differ in their ECF risk and livestock systems. At each site, focus -group meetings were held to explore farther perceptions of ECF risk, ECF control methods used, and what variables farmers feel increase the risk of ECF and its control measures. The range of these variables and their relative rankings were assembled and the relative risk rankings compared to independent estimates of biological risk These "perceived-risk" variables were also used to design a study investigating variations in risk perceptions and tile adoption of ECF control measures among individual farmers. Results of the farmer-level risk perception assessment are aggregated by agro-ecological zone and production system. This information will be combined with estimates of the biological risk for ECF and its control in developing strategies to enhance the delivery and adoption of appropriate control strategies for each of the major agro-ecological zones and smallholder production systems.